Fight obesity app: a proof-of-concept prototype of mobile game-based treatment / Wang Yanzhen, Tan Wee Hoe and Maizatul Hayati Mohamad Yatim - Wang, Yanzhen; Tan, Wee Hoe; Mohamad Yatim, Maizatul Hayati (UiTM Press, 2016)
This paper presents how a mobile game was designed and developed in an education research laboratory as a proof-of-concept for treating obesity in preschool children. It depicts how a pediatrician cooperated with game based learning researchers to produce a mobile app for a game based obesity treatment. The intention of the pediatrician was to guide preschool children between the ages of three to six years old, to understand the concept of childhood overweight and obesity, while keeping in mind the long term consequences of obesity, and how to choose healthy food in Malaysian daily living contexts. The interdisciplinary cooperation between these individuals resulted the creation of the Fight Obesity 2.0 mobile app. The mobile app has been featured through tablet computer as a platform to gamify healthcare education contents for toddlers and young children. The major difficulty faced in the game production was determining the modality of multimedia content presentation and selecting appropriate pedagogical approaches for preschool children. This paper illustrates how the difficulty was overcome and reflects lessons learned from the interdisciplinary cooperation. The experience shown in the study would benefit professionals in medicine, preschool education and game experts who are interested in initiating cross- disciplinary cooperation for making treatment of obesity fun, engaging and meaningful for children.